Potential Implementation of Android-Based Interactive Multimedia for Student Learning Activities - Khotimatunnisa Utami; Muhammad Akhyar; Sudiyanto Sudiyanto (STAI Hubbulwathan Duri, 2023)
The development of technology in the field of 21st century education has become the main complement in the teaching and learning process. Various innovations were created to support learning activities such as the use of android technology. The emergence of COVID-19 makes interactive multimedia based on Android very important to help students and teachers achieve maximum learning. The purpose of this study was to determine students' perceptions of the use of Android-based interactive multimedia in learning mathematics during the covid-19 period. This study used a survey research method using a questionnaire which involved 53 randomly selected fifth grade elementary school students. The data collection technique was carried out using a questionnaire which was distributed to a sample of the fifth grade elementary school student population. From the results of the study, it showed that 91% of students had never used interactive multimedia based on Android while 9% had used it. Data on student perceptions of the use of media during online learning shows that 85% of students agree to adopt interactive multimedia, 9% of students agree to adopt audio-visual media, and 6% agree to adopt visual media. The results of this research succeeded in identifying that most students had never used interactive multimedia during learning activities, even though in fact and interest, it turned out that students were willing to carry out the learning process using interactive multimedia, as evidenced by the results of a survey conducted regarding the types of media they agreed to adopt. The results of this research can be used as a basis for developing an instructional product in an interactive multimedia format.